Increasing the Effectiveness of Higher Education Academic Services Through the Implementation of the Chatbot Platform Using the SVM Machine Learning Algorithm - Setiyani , Lila (Universitas Pendidikan Ganesha, 2023)
The education sector has adopted technology and digitization. To create appropriate technology that can increase the effectiveness and efficiency of existing processes in education, especially higher education, innovations are needed that can provide value to tertiary institutions. The right support is needed to achieve value in academic services as the heart of higher education. However, many universities still have not been able to provide maximum service. This research aims to create a chatbot model to support effective academic services for tertiary institutions. This research belongs to the type of research design science research (DSR). The research procedures were carried out by collecting data, categorizing data, creating chatbot models, model evaluation, and model implementation. Data was collected by inviting resource persons through focus group discussions (FGD), with the criteria being prospective students, university students, and the public interested in academic services in tertiary institutions. The resource persons were asked questions about the academic services needed. Based on the data obtained, there were 257 questions related to academic services. Service categorization is the process of classifying questions based on the functions of divisions or departments in tertiary institutions. Based on the data collection and service categorization results, a chatbot model is created, followed by model evaluation and implementation. The research analysis results show that the academic management chatbot model that uses the SVM algorithm can classify questions asked through chatbots with an accuracy of 57%, performing to support higher education academic services.